"Enthusiasm, " "Passion, " and Religious Conversion in the Scottish Enlightenment. (4th May 2021) - Shaw, Ian J.
Abstract : This article analyses the first‐hand accounts of those involved in the 1742 religious revivals in the Scottish parishes of Cambuslang and Kilsyth, particularly those of the parish ministers William McCulloch and James Robe. Although the events were accompanied by dramatic manifestations, with some participants crying out, violently trembling, or falling to the ground, the key focus of interest was on religious conversion. Supporters of the revival sought to create a religious discourse that dealt with criticisms that events were manifestations of "enthusiasm" and unrestrained "passions." Their accounts drew not only on Reformation and Puritan idioms and approaches but also those of the moderate Enlightenment in an attempt to demonstrate that the events were factual, reasonable, and conformed to Scripture. In their detailed and careful records, McCulloch and Robe were particularly concerned with evaluating the difference between genuine and spurious religious experience. Their approach was shaped by that of Jonathan Edwards. This research supports the contention that in eighteenth‐century Scotland a series of enlightenment religious discourses developed, and these included a distinctive evangelical version. This was, however, contested, being subjected to critique not only by opponents of the revival but also by others in the evangelical community.